Improving the Interviewing of Suspects Using the PEACE Model: a Comprehensive Overview - Bull, Ray (Canadian journal of criminology and criminal justice, 2023)
In light of psychological research, a growing number of countries/organizations have decided to adopt a model/approach of "investigative interviewing" of suspects that does not rely on coercive or oppressive methods. In 2016, the United Nations’ "Special Rapporteur on torture and other cruel, inhumane or degrading treatments" (law professor Juan Mendez) submitted his report to the United Nations, which stated that "The Special Rapporteur … advocates the development of a universal protocol identifying a set of standards for non-coercive interviewing methods and procedural safeguards that ought, as a matter of law and policy, to be applied at a minimum to all interviews by law enforcement officials, military and intelligence personnel and other bodies with investigative mandates." When mentioning this "universal protocol" in 2016, the U.N. Special Rapporteur noted that "The essence of an alternative information-gathering model was first captured by the PEACE model of interviewing adopted in 1992 in England and Wales … investigative interviewing can provide positive guidance for the protocol." The "universal protocol" took three years to produce and was published in 2021. This article will overview (i) the evolution of the PEACE method, (ii) some of the research on effectiveness of aspects of the PEACE method, and (iii) the 2021 publication called Principles of Effective Interviewing.